Global conformation of Tau protein mapped by Raman spectroscopy - Gorantla, N.V.; Khandelwal, P.; Poddar, P.; Chinnathambi, S. (Methods in Molecular Biology, 2017)
Alzheimer’s disease (AD) is one of the neurodegenerative disease characterized by progressive neuronal loss in the brain. Its two major hallmarks are extracellular senile plaques and intracellular neurofibrillary tangles (NFTs), formed by aggregation of amyloid β-42 (Aβ-42) and Tau protein respectively. Aβ-42 is a transmembrane protein, which is produced after the sequential action of β- and γ-secretases, thus obtained peptide is released extracellularly and gets deposited on the neuron forming senile plaques. NFTs are composed of microtubule-associated protein-Tau (MAPT). Tau protein’s major function is to stabilize the microtubule that provides a track on which the cargo proteins are shuttled and the stabilized microtubule also maintains shape and integrity of the neuronal cell. Tau protein is subjected to various modifications such as phosphorylation, ubiquitination, glycation, acetylation, truncation, glycosylation, deamination, and oxidation; these modifications ultimately lead to its aggregation. Phosphorylation is the major modification and is extensively studied with respect to Tau protein. Tau protein, however, undergoes certain level of phosphorylation and dephosphorylation, which regulates its affinity for microtubule and ultimately leading to microtubule assembly and disassembly. Our main aim was to study the native state of longest isoform of Tau (hTau40WT-4R2N) and its shortest isoform, (hTau23WT-3R0N), at various temperatures such as 10, 25, and 37 °C. Raman spectroscopic results suggested that the proportion of random coils or unordered structure depends on the temperature of the protein environment. Upon increase in the temperature from 10 to 37 °C, the proportion of random coils or unordered structures increased in the case of hTau40WT. However, we did not find a significant effect of temperature on the structure of hTau23WT. This current approach enables one to analyze the global conformation of soluble Tau in solution.

Surface disordered rutile TiO2-graphene quantum dot hybrids: a new multifunctional material with superior photocatalytic and biofilm eradication properties - Biswas, A.; Salunke, G.; Khandelwal, P.; Das, R.; Poddar, P. (New Journal of Chemistry, 2017)
The controlled introduction of defects in semiconductors has contributed to the development of electronic devices and technologies. Recently, chemical control over defects, formation of new hybrid materials and multifunctional nanostructures have been sought in energy, health, and environment related technologies. Surface-disordered anatase-TiO2 has received wide attention due to its exceptional photocatalytic performance. Herein, we demonstrate, for the first time, a one-step aqueous-phase synthesis of a surface-disordered rutile TiO2-graphene quantum dot (TG) hybrid material. The TG-hybrid is a rutile-TiO2 matrix in which homogeneous in situ insertion of GQDs occurs during the growth of the TiO2 particles. The TG-hybrid material showed superior photocatalytic performance with similar to 98% solar light driven photo-degradation of methylene blue (MB) dye within 6 min and similar to 86% of rhodamine-B (RhB) within 4 min which is much better than the photocatalytic performance shown by the rutile-TiO2 (similar to 30% and similar to 20%, respectively) and GQDs (similar to 15% and similar to 8%, respectively), themselves. Moreover, the TG-hybrid also showed enhanced toxicity to Gram-positive (S. aureus) as well as Gram-negative (E. coli, P. aeruginosa) bacterial cells. The growth-curves of E. coli cells, after incubating them with increasing concentrations of the TG-hybrid, showed that the TG-hybrid could effectively inhibit the growth of E. coli cells at a concentration of 60 mu g mL(-1). The effect of UV-light exposure on the bacterial-biofilm disruption by the TG-hybrid material was also investigated. It was observed that in the presence of UV-light, the biofilm disruption done by the TG-hybrid was larger in comparison to the TiO2 and GQDs alone, under the same conditions. The increase in the formation of reactive oxygen species (ROS) in the presence of sunlight for the TG-hybrid may be the reason behind its superior antibacterial and biofilm eradication properties. We believe that the TG-hybrid material will have applications in energy, health and environment related technologies.